Comparison of UV/H2O2, UV/PMS, and UV/PDS in Destruction of Different Reactivity Compounds and Formation of Bromate and Chlorate - Guan, Ying-Hong; Chen, Jin; Chen, Li-Jun; Jiang, Xin-Xin; Fu, Qiang (Frontiers in Chemistry, 2020)
In this study, we compared the decontamination kinetics of various target compounds and the oxidation by-products (bromate and chlorate) of PMS, PDS, and H2O2 under UV irradiation (UV/PMS, UV/PDS, UV/H2O2). Probes of different reactivity with hydroxyl and sulfate radicals, such as benzoic acid (BA), nitrobenzene (NB) and trichloroethane (TCM), were selected to compare the decontamination efficiency of the three oxidation systems . Experiments were performed under acidic, neutral and alkaline pH conditions to obtain a full-scale comparison of UV/peroxides. Furthermore, the decontamination efficiency was also compared in the presence of common radical scavengers in water bodies (bicarbonate, carbonate and NOM). Finally, the formation of oxidation by-products, bromate and chlorate, was also monitored in comparison in the pure water and tap water. Results showed that UV/H2O2 showed higher decontamination efficiency than UV/PDS and UV/PMS for BA degradation while UV/ H2O2 and UV/PMS showed better decontamination performance than UV/PDS for NB degradation under acidic and neutral condition. And UV/PMS was the most efficient among the three processes for BA and NB degradation under alkaline condition. Whilst, UV/PDS was the most efficient for TCM degradation under all pH conditions. In pure water, both bromate and chlorate were formed in UV/PDS, small amount bromate and rare chlorate was observed in UV/PMS, and no detectable bromate and chlorate was formed in UV/H2O2. In tap water, no bromate and chlorate was detectable for all three systems.